Variability studies in fennel (Foeniculum vulgare Mill.) - Y Yadav, P S Yadav, V P Pandey, (Journal of Spices and Aromatic Crops, 2013)
Analysis of variability carried out for nine characters in 25 diverse genotypes of fennel (Foeniculum vulgare) revealed high genotypic and phenotypic coefficient of variations for seed yield plant-1, weight of grains umbel-1, number of umbels plant-1, number of branches plant-1, number of umbellet umbel-1 and plant height. Heritability estimates were high for test weight, weight of grains umbel-1, seed yield plant-1, number of umbel plant-1, plant height and number of umbelletes umbel-1. Higher genetic advance as per percentage of mean was recorded for seed yield plant-1, weight of grains umbel-1, number of umbels plant-1, number of branches plant-1, number of umbelletes umbel-1, plant height and test weight. The plant height, days to 50% flowering, number of branches plant-1, number of umbels plant-1, number of umbellets umbel-1 and weight of grains umbel-1 exhibited positive and significant correlation with seed yield. Path coefficient analysis revealed that days to maturity had highest direct effect on seed yield followed by days to 50% flowering and number of umbels plant-1. Therefore, greater emphasis should be given on these characters while selecting for higher yield and related traits.